Electron impact fragmentation of pyrrole molecules studied by fluorescence emission spectroscopy - Wasowicz, Tomasz; Linert, Ireneusz; Lachowicz, Izabela; Zubek, Mariusz (Photonics Letters of Poland, 2011)
The fluorescence emission spectroscopy using electron impact excitation technique was employed to study fragmentation processes of the gas phase pyrrole molecules. The following excited fragmentation species were observed by detection of their fluorescence decay: the atomic hydrogen H(n), n = 4?7 and the diatomic CH(A2?), CN(B2?+), NH(A3?) and C2(d3?g) fragments. These atomic and molecular products differ from those previously reported in fragmentation of pyrrole and their identification gives a new insight into dissociation and fragmentation channels of the excited states of pyrrole molecules. | Full Text: PDF References L. Sanche, "Low energy electron-driven damage in biomolecules", Eur. Phys. J. D 35, 367 (2005)[CrossRef] G. Hanel et al., "Electron Attachment to Uracil: Effective Destruction at Subexcitation Energies", Phys. Rev. Lett. 90, 188104 (2003)[CrossRef] H. Abdoul-Carime, S. Gohlke, E. Illenberger, "Site-Specific Dissociation of DNA Bases by Slow Electrons at Early Stages of Irradiation", Phys. Rev. Lett. 92, 168103 (2004)[CrossRef] A.L. Sobolewski, W. Domcke, C. Dedonder-Lardeux, C. Jouvet, "Excited-state hydrogen detachment and hydrogen transfer driven by repulsive 1* states: A new paradigm for nonradiative decay in aromatic biomolecules", Phys. Chem. Chem. Phys. 4, 1093 (2002)[CrossRef] M.N.R. Ashfold et al., "??* excited states in molecular photochemistry", Phys. Chem. Chem. Phys. 12, 1218 (2010)[CrossRef] A. Lifshitz, C. Tamburu, A. Suslensky, "Isomerization and decomposition of pyrrole at elevated temperatures: studies with a single-pulse shock tube", J. Phys. Chem. 93, 5802 (1989)[CrossRef] J.C. Mackie, M.B. Colket III, P.F. Nelson, M. Esler, "Shock tube pyrolysis of pyrrole and kinetic modeling", Int. J. Chem. Kinet. 23, 733 (1991)[CrossRef] F. Dubnikova, A. Lifshitz, "Isomerization of Pyrrole. Quantum Chemical Calculations and Kinetic Modeling", J. Phys. Chem. A 102, 10880 (1998)[CrossRef] L. Zhai, X. Zhou, R. Liu, "A Theoretical Study of Pyrolysis Mechanisms of Pyrrole", J. Phys. Chem. A 103, 3917 (1999)[CrossRef] M. Martoprawiro, G.B. Bacskay, J.C. Mackie, "Ab Initio Quantum Chemical and Kinetic Modeling Study of the Pyrolysis Kinetics of Pyrrole", J. Phys. Chem. A 103, 3923 (1999)[CrossRef] D.A. Blank, S.W. North, Y.T. Lee, "The ultraviolet photodissociation dynamics of pyrrole", Chem. Phys, 187, 35 (1994)[CrossRef] H. Lippert, H.H. Ritze, I.V. Hertel, W. Radloff, "Femtosecond Time-Resolved Hydrogen-Atom Elimination from Photoexcited Pyrrole Molecules", Chem. Phys. Chem. 5, 1423 (2004)[CrossRef] M. Dampc, M. Zubek, "Dissociation and fragmentation of furan by electron impact", Int. J. Mass Spectrom. 277, 52 (2008)[CrossRef] I. Linert, I. Lachowicz, T.J. Wasowicz, M. Zubek, "Fragmentation of isoxazole molecules by electron impact in the energy range 10?85 eV", Chem. Phys. Lett. 498, 27 (2010)[CrossRef] J. Wei, A. Kuczmann, J. Riedel, F. Renth, F. Temps, "Photofragment velocity map imaging of H atom elimination in the first excited state of pyrrole", Phys. Chem. Chem. Phys. 5, 315 (2003)[CrossRef] G. da Silva, E.E. Moore, J.W. Bozzelli, "Quantum Chemical Study of the Structure and Thermochemistry of the Five-Membered Nitrogen-Containing Heterocycles and Their Anions and Radicals", J. Phys. Chem. A 110, 13979 (2006)[CrossRef] S.J. Blanksby, G.B. Ellison, "Bond Dissociation Energies of Organic Molecules", Acc. Chem. Res. 36, 255 (2003)[CrossRef] D.R. Lide, Handbook of Chemistry and Physics (CRC Press, Boca Raton 2004).